The art and science of teaching - Adams, Gregg; Brown, John L.; Welch, Leslie; Association for Supervision and Curriculum Development (Alexandria, Va. : ASCD, 2008)
This video set guides viewers through classroom examples of effective instructional strategies includes: establishing and communicating learning goals, tracking student progress, celebrating success, helping g students interact with new knowledge, help students practice and deepen their understanding, generate and test hypotheses, engaging students, establishing and maintaining rules and procedures, creating and maintaining effective relationships with students, and communicating high expectation for all students.
Part 1: Effective instructional strategies (ca. 32 min.) -- Part 2.: Effective classroom management strategies (ca. 32 min.).
Consultant, Robert J. Marzano ; editor/motion graphics, Adam Welch ; content expert, John L. Brown.
DVD format
Keywords: Effective teaching -- United States; School supervision -- United States; Classroom management -- United States; Learning, Psychology of